PEMANFAATAN IOT JERAMI PADI-KOPI UNTUK BUDIDAYA JAMUR MERANG (JADI-JARANG) PAADA KELOMPOK TANI TUNAS BARU - Risnaini masda Masdalipa; Dedi Setiadi; Edowinsyah Edowinsyah (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2025)
Agricultural residues such as rice straw and coffee husks are often underutilized, despite their potential as cultivation media for straw mushroom (Volvariella volvacea). This study aimed to develop a rice straw–coffee husk-based cultivation model (Jadi-Jarang) within the Tunas Baru Farmer Group to promote business diversification, increase farmers’ income, and encourage environmentally friendly waste management. The cultivation process included media preparation, fermentation, spawn inoculation, mushroom house maintenance, harvesting, and post-harvest handling. Evaluations were carried out on mycelium growth, mushroom productivity, product quality, and socio-economic impacts. Results indicated that the combination of rice straw and coffee husks effectively supported mushroom growth, with evenly distributed mycelium, relatively short harvesting time (14–18 days), and fresh mushrooms of high market value. Moreover, this initiative enhanced farmers’ skills, reduced agricultural waste, and provided additional income. Therefore, the rice straw–coffee husk model offers both economic benefits and sustainable farming practices based on zero waste farming, making it a promising approach for farmer groups.